'Oh Joy, Oh Rapture': The Oily Chart Opera Company reflects the enduring charm of Gilbert and Sullivan in South Africa. Issue 2 (4th May 2018) - Page-Shipp, Roy; Joseph, Dawn; van Niekerk, Caroline
ABSTRACT: For over four decades 'The Oily Chart Opera Company' have annually produced and performed a Gilbert and Sullivan Savoy opera in Pretoria, South Africa. In this strictly amateur group, designed to allow busy people to participate over six to seven weeks, members undertake all the roles on stage as well as making costumes and stage sets. Unique to the group is a single music 'coach and accompanist' having served for 45 years and many of the current members having performed in all of the Gilbert and Sullivan operas more than once. Data was gathered in a survey forming part of a research project Spirituality and Well-being: Music in the community. Interpretative Phenomenological Analysis was used to code the data into four broad themes: Joining, Learning and Leadership, Benefits of Community Music, Connections to Well-being and Spiritual Connections. The findings show the typical benefits experienced by those who perform regularly in groups, although this group draws special joy from their strict focus on Gilbert and Sullivan's operas. They also understand the spiritual connection to their music in the familiar dual categories of religious and secular spirituality. This particular group of performers is keeping Savoy operas alive in modern-day sub-Saharan Africa.